Segregación escolar público-privado por nivel socioeconómico en Uruguay: Un análisis en base a microdescomposiciones - Lucía Ramírez Leira (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2021)
This paper analyzes school segregation according to socioeconomic level between public and private schools in Uruguay during the 1992-2017 period. Using microdata from household surveys, the measurements provide empirical evidence of a significant increase in segregation, especially during the last 15 years, for both the primary and secondary education levels. Applying a micro-decomposition methodology to explore the determinants of increasing segregation, the results suggest that changes in the observable characteristics of individuals, mainly the households's income, account for most of the variation in educational segregation experienced in recent decades. Furthermore, a greater propensity to choose private schools seems to have played a relevant role in the observed change, especially at the secondary education level, possibly liked to an increase in the perceived quality gap between both educational sub-systems.
Keywords: 330; segregation; education; microdescomposition; Uruguay